Modification of ceramic membrane surface by nanoparticle coating for improved wettability during oil-water separation - Maome, Tshepo G. (Vaal University of Technology, 2022)
The developed oil-water separation membranes used in membrane technology are currently inefficient due to their poor morphological and topographical properties during nanoparticle coating. Researchers have developed different wettable membrane surfaces using jet spray coating. Most of these developed membranes are inadequate due to poor morphological and topographical properties normally observed as clusters, creating a rougher membrane surface that hinders wettability. This has resulted in the existing membrane fouling and degradation during the oil/water separation process and again due to different responses to corrosion and rusting. In the current study, membrane clusters were minimised on the ceramic membranes to create a smoother surface, improving membrane wettability. These clusters were minmised at optimal coating force, optimal coating distance and optimal coating angle. Part one of the study was to model and simulate different parameters that decreased clusters using the jet-spray coating. A theoretical model was derived from the first principles and all the external and internal forces that impact membrane clusters were considered during the model derivation. These forces are the force due to applied pressure from the spray gun, the force of nano-particles, the force of viscosity, the upward force on solid wall due to nanoparticles, the downward force on solid wall due to nanoparticles and the reaction force on the solid wall due to nanoparticles. The tools of stochastic theory and the concept of fluid dynamics were used in the modelling process. The total coating force from the jet spray gun nozzle was increased from 0,2x107 kN to 2,4x107 kN, which gave optimal coating force. The coating distance from the jet spray gun nozzle to the membrane surface was increased from 10 mm to 24 mm, which gave optimal coating distance. The jet spray angle in the spray region was also increased from 1⁰ to 9⁰ with reference from the vertical axis to the membrane surface, which gave optimal coating angle. This lead to optimal spread of nanoparticles on the membrane surface thus resulting to optimal cluster minimisation during the coating process. This decreased cluster sizes during nanoparticle coating, resulting in a smooth membrane surface, thus leading to lowered surface energy on the membrane. Part two of the study was to fabricate the ceramic membrane with fewer clusters on the surface for improved wettability using the jet-spray coating. It was important to produce the ceramic membrane surfaces with minimised membrane clusters by considering the optimal parameters revealed to minimise these membrane clusters during coating. Nanoparticle coating was performed under a controlled laboratory environment, and the optimal parameters that were studied to minimise membrane clusters were revealed. These parameters are coating force, coating distance and coating angle. More coating rounds were applied on ceramic samples and clusters were minimised during these coating rounds. The coated samples were analyzed by a scanning electron microscope and the nanoparticles on the membrane surfaces were characterised for optimal performance during oil-water separation. The scattering, orientation, morphology, spatial distribution, surface roughness, surface smoothness, contact angles, surface density of the particles, pore size network, mean size of the coated nanoparticle on the membrane surface after different coating rounds were characterised and analysed to minimise membrane cluster during nanoparticle coating. It was shown that more clusters were observed in 1st LP, 2nd LP, 3rd LP and 4th LP coating rounds when compared to 1st HP, 2nd HP, 3rd HP and 4th HP coating rounds. It was also shown that material surface roughness increased the formation of clusters in membrane surface as more clusters were observed in rough membrane surface when compared to the smooth membrane surface. The microstructure revealed a smoother membrane surface where membrane clusters were minimised. Part three of the study was to compare the newly designed ceramic membrane with the previously designed ceramic membrane from previous the literature. The correlation was done on the experimental results obtained in this study with the experimental results obtained from the previous literature. Different coating rounds were performed from the current study and the previous literature to design nanostructured ceramic membranes with fewer clusters on the surface. The results in the last coating round in this study, revealed a smooth membrane with a homogeneous substrate with fewer clusters and small sizes compared to other coating rounds.
M. Eng. (Department of Mechanical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Clusters; Wettability; Ceramics; Nanoparticle coating; Surface energy; Surface tension; Dissertations, Academic -- South Africa.; Nanoparticles.; Ceramic membranes.; Oil separators.